A History of the Essay and the Havoc It Wreaked (KULT_online, 2019)
Rather than aiming at a unified definition or portrayal of the essay genre, this edited volume seeks to investigate some of the various forms and transformations in which the essay has appeared throughout different time periods and cultures. Indeed, most articles come up with highly significant insights about the essay and succeed in illuminating the genre from alternative and non-canonical perspectives, e.g. by describing certain texts as essays which so far have not been subsumed under this label. Yet the compilation could have tackled the diverse fields it seeks to cover in a more representative manner.